Microstructure and phase stability of suspension high velocity oxy-fuel sprayed yttria stabilised zirconia coatings from aqueous and ethanol based suspensions - Bai, M.; Maher, H.; Pala, Z.; Hussain, Tanvir (Elsevier, 2017)
Two commercial 7-8 wt.% Yttria Stabilised Zirconia (YSZ) suspensions were sprayed by Suspension High Velocity Oxy Fuel (SHVOF) thermal spraying for advanced high temperature coatings. Heat treatments of the free-standing coatings were conducted at 800 °C and 1000 °C for 72 h. The SHVOF coatings using two liquid carriers: water and ethanol, behaved differently in terms of micro-structure and phase stability. The ethanol coatings retained a fully tetragonal composition after heat treatments; while the aqueous coatings, however, underwent the undesirable tetragonal to monoclinic phase transformation at 1000 °C, which is lower than previously reported temperatures (>1200 °C) in thermal sprayed YSZ coatings. The heat treatments not only resulted in densification of both coatings, but also caused excessive crystallite growth in aqueous coatings promoting the undesirable phase transformation. On the contrary, the ethanol suspension improved the phase stability by favouring the homogenization of yttrium during spraying.